2010
DOI: 10.1111/j.1538-7836.2010.03816.x
|View full text |Cite
|
Sign up to set email alerts
|

Generation and characterization of inhibitory nanobodies towards thrombin activatable fibrinolysis inhibitor

Abstract: To cite this article: Buelens K, Hassanzadeh-Ghassabeh G, Muyldermans S, Gils A, Declerck PJ. Generation and characterization of inhibitory nanobodies towards thrombin activatable fibrinolysis inhibitor. J Thromb Haemost 2010; 8: 1302-12.Summary. Background and objective: As activated thrombinactivatable fibrinolysis inhibitor (TAFIa) is a potent antifibrinolytic enzyme, the development of TAFI inhibitors is a new promising approach in the development of profibrinolytic drugs. We, therefore, aimed to generate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 50 publications
2
69
0
Order By: Relevance
“…TAFI is a procarboxypeptidase activated by plasmin, the thrombin-TM complex, and trypsin-like enzymes to remove exposed terminal lysines from fibrin which are needed for plasmin formation. A recent study from Buelens et al (51) provides a novel approach to inhibiting TAFIa and promoting fibrinolysis using nanobodies. A nanobody is a singlechain monomeric antigen-binding immunoglobulin, naturally devoid of light chains, found uniquely in camelids (llama, alpaca, and Bactrian camels) (150).…”
Section: B Targeting Coagulopathy In Sepsismentioning
confidence: 98%
See 1 more Smart Citation
“…TAFI is a procarboxypeptidase activated by plasmin, the thrombin-TM complex, and trypsin-like enzymes to remove exposed terminal lysines from fibrin which are needed for plasmin formation. A recent study from Buelens et al (51) provides a novel approach to inhibiting TAFIa and promoting fibrinolysis using nanobodies. A nanobody is a singlechain monomeric antigen-binding immunoglobulin, naturally devoid of light chains, found uniquely in camelids (llama, alpaca, and Bactrian camels) (150).…”
Section: B Targeting Coagulopathy In Sepsismentioning
confidence: 98%
“…A nanobody is a singlechain monomeric antigen-binding immunoglobulin, naturally devoid of light chains, found uniquely in camelids (llama, alpaca, and Bactrian camels) (150). Nanobodies from an alpaca immunized with TAFIa showed broad specificity and sensitivity for functional inhibition of TAFI activation and good penetration into the clot (51). The small size of nanobodies (15 kDa) with relatively low immunoge- .…”
Section: B Targeting Coagulopathy In Sepsismentioning
confidence: 99%
“…An alternative anti-TAFI approach by Buelens et al created a panel of inhibitory nanobodies effective against the various modes of TAFI activation and activity. Nanobodies are single domain antibodies from the sera of members of the Camilidae family which have advantageous properties such as low immunogenicity and high affinity, solubility and stability [150]. Two nanobodies showed a potent profibrinolytic effect in an in vitro clot lysis assay and their interaction with TAFI was later characterised using X-ray crystallography.…”
Section: Current Approaches To Reduce Hypofibrinolysis In Diabetesmentioning
confidence: 99%
“…A TAFIa activity assay demonstrated that VHH‐i83 inhibited TAFIa activity in a dose‐dependent manner (Fig. C) ). However, this observation could not be readily explained by the structure of TAFI–VHH‐i83, as VHH‐i83 mainly interacts with the AP and does not bind close to the active site cleft in the CM (Fig.…”
Section: Resultsmentioning
confidence: 91%